Stress relief behaviour of diamond-like carbon films on glasses - Lee, Kwang-Ryeol; Baik, Young-Joon; Eun, Kwang-Yong (Publ by Elsevier Sequoia SA, Lausanne, Switzerland, 1993)
The stress relief behaviour of diamond-like carbon (DLC) films on glass substrates was investigated. The r.f.-plasma-enhanced chemical vapour deposition method was used for the deposition with variable negative bias voltages of the cathode from -100 to -700 V. Beyond a critical thickness of the film, film delamination starts to occur after its removal from the reaction chamber. In addition to the previously observed stress relief morphologies, sinusoidal cracking and sinusoidal removal of the film are also observed. The stress relief morphology is dependent on the film thickness and the negative bias voltage. The measured wavelength of sinusoidal buckling increases with both increasing film thickness and increasing negative bias voltage. This behaviour is qualitatively consistent with a phenomenological equation derived by Nir. It was suggested that the elastic modulus of the DLC film can be calculated using the dependence of the wavelength of sinusoidal buckling on the film thickness and the negative bias voltage.